Android-Based Technology: Development of Alternative and Augmentative Mi-Says Communication Systems for Children with Intellectual Disabilities - Alya Jilan Rizqita (Universitas Pendidikan Indonesia (UPI), 2022)
This study aims to developed an android-based alternative and augmentative communication system to children intellectual disability with communication difficulted. This research method used a qualitative descriptive method to explore the information. The sample of this research is children with intellectual disabilities with complex communication needs. The result of this research is the developed of an alternative and augmentative communication system using Android-based technology called